EPIDEMIOLOGY OF SMEAR - NEGATIVE TUBERCULOSIS IN IBADAN, NIGERIA - Kehinde, Oludiran Aderemi; Dada-Adegbola, Hannah (African Journal of Infectious Diseases (AJID), 2013)
Inadequate case detection has been identified as one of the reasons for high burden of tuberculosis (TB) in the world especially in poor resourced countries of Africa and Asia. This retrospective laboratory study involving the review of specimens processed at the TB laboratory of the Department of Medical Microbiology and Parasitology, University College Hospital, Ibadan, Nigeria was carried out over a period of five years (January 2006-December 2010) to access the epidemiology of smear- negative TB. Of the 3468 specimens processed, 2,175 (62.7%) were from males while a lower percentage (37.3%)1293 were from females, giving a M:F = 1:0.37. Over half of the specimens, 2,046 (59.0%) were from patients aged 21 to 60 years, 392 (11.3%) from 11 to 20 years, 825 (23.8%) from 60 years and above while 205 (5.9%) were from age 1-10 years. Most of the 2,663 (76.8%) specimens processed were sputum while 201 (5.8%) were gastric washings. Three hundred and nine (8.9%) were smear positive while 392 (11.3%) out of the 3468 specimens processed were culture positive. However, 83 (2.6%) of the 3159 smear-negative specimens were culture positive (false negative) while 66 (21.4%) of the 309 smear- positive specimens were negative for culture (false positive). The majority, 3010 (86.8%) were smear and culture negative while 309 (8.9%) were positive for both tests. Of the 83 false negative specimens, 51 were sputum samples representing (61.4%), 19 (22.9%) were gastric washings while 13 (15.7%) were from extra-pulmonary sites (CSF, aspirates, ascitic fluids, etc). The findings of 2.6% smear-negative but culture positive (false negative) specimens in this study reveals that culture of specimens in addition to smear microscopy from suspected cases is necessary as a diagnostic /confirmatory tool for tuberculosis.